INTERNAL AND EXTERNAL ATTRIBUTIONS AS DETERMINANTS OF ATHLETES` HIGH PERFORMANCE IN INDIVIDUAL AND TEAM SPORTS IN SELECTED TERTIARY INSTITUTIONS, SOUTHWEST, NIGERIA - Okwong, OKON Emmanuel (Advances in Social Sciences Research Journal, 2019)
The study was designed to investigate relationship of internal and external attributions on high performance in individual and team sports in tertiary institutions athletes to redress low performance of athletes. To achieve the purpose of the study, student athletes of tertiary institutions in southwest states, Nigeria, who had participated in inter-colligate sports competitions were examined, These four hundred and sixty-three athletes made up of 206 in individual and 257 in team sports were selected as participants. Multi-stage sampling technique was used to select states through convenience sampling technique, institutions through simple random sampling technique, sports through purposive sampling technique, and high performer athletes were determined by their position ranking of 1st -3rd secured during sport competitions. The instruments designed to measure internal and external attributions responses of the respondents was Rotter`s I-E developed by Rotter (1966). The statistical analysis of Pearson`s Product Moment Correlation, Regression were used to test the relationship at significance level of 0.05 levels. The finding of the study showed that each internal and external attributions revealed no significant relationship to high performance. Rather, coaches and athletes need to be informed, the consequent effect of attributions to either high or low performance before, during and after sport competitions